Teachers' self-efficacy and intercultural classroom practices in diverse classroom contexts: A cross-national comparison. (November 2020) - Romijn, Bodine R.; Slot, Pauline L.; Leseman, Paul. P.M.; Pagani, Valentina
Highlights: We examined teacher self-efficacy in a cross-national setting. Teacher self-efficacy can be viewed as a two-dimensional concept. Both general and diversity-related domain-specific efficacy beliefs were measured. Diversity-related beliefs are positively related to intercultural classroom practices. Teacher-efficacy and practices are affected by diversity in the classroom context. Abstract: This cross-national study provides new insights in teacher efficacy in today's culturally diverse classrooms using survey data of 269 early childhood and primary school teachers in England, Italy, the Netherlands and Poland. Teacher efficacy can be viewed as a two dimensional concept in which both general beliefs are measured alongside (diversity-related) domain-specific beliefs. These beliefs are related to the cultural classroom context and the use of intercultural classroom practices. Our results indicate that policies and professional development targeted at the reciprocal relation between diversity-related efficacy and practices are important when preparing teachers for working in diverse classroom contexts.